2008
DOI: 10.1103/physrevlett.100.196401
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale High Energetic Materials: A Polymeric Nitrogen ChainN8Confined inside a Carbon Nanotube

Abstract: We present a theoretical study of a new hybrid material, nanostructured polymeric nitrogen, where a polymeric nitrogen chain is encapsulated in a carbon nanotube. The electronic and structural properties of the new system are studied by means of ab initio electronic structure and molecular dynamics calculations. Finite temperature simulations demonstrate the stability of this nitrogen phase at ambient pressure and room temperature using carbon nanotube confinement. This nanostructured confinement may open a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 19 publications
6
73
0
Order By: Relevance
“…If proven experimentally viable, it may open a new path towards stabilization of polynitrogen or polymeric nitrogen compounds under ambient conditions. 316, 317 An energy barrier of 1.07 eV was found for the formation of N 8 / CNT (5,5) from N 2 /CNT (5,5), while the dissociation barrier was 0.2 eV. Reaction pathway snapshots have shown that the transition state is composed of N 2 and N 6 inside a CNT (5,5).…”
Section: Stabilization and Desensitization Of Ems By Cnmsmentioning
confidence: 95%
See 1 more Smart Citation
“…If proven experimentally viable, it may open a new path towards stabilization of polynitrogen or polymeric nitrogen compounds under ambient conditions. 316, 317 An energy barrier of 1.07 eV was found for the formation of N 8 / CNT (5,5) from N 2 /CNT (5,5), while the dissociation barrier was 0.2 eV. Reaction pathway snapshots have shown that the transition state is composed of N 2 and N 6 inside a CNT (5,5).…”
Section: Stabilization and Desensitization Of Ems By Cnmsmentioning
confidence: 95%
“…This inclusion process stabilizes the highly energetic polynitrogen chain, which is unstable under ambient conditions. 237 This approach helps in the utilization of highly unstable EMs.…”
Section: Ems Based On Functionalized Cntsmentioning
confidence: 99%
“…[2] Density functional theory (DFT) has been used to show that a N 8 single zigzag chain of nitrogen atoms is stable inside carbon nanotubes and between sheets of graphene. [3] A novel approach to the isolation of a polynitrogen phase that would be stable at ambient conditions is suggested by the work of Abou-Rachid et al [4] (see Figure S1 in the Supporting Information). Owens however predicted with DFT calculations that a double chain (N 2 ) 12 oligomer would be stable under ambient conditions without carbon nanotube or graphene sheets.…”
mentioning
confidence: 98%
“…N 3 , N 4 , N 5 or their ions were experimentally detected under high-pressure and high-temperature conditions. Herein, a N 8 À PN stabilized on the positively charged sidewalls of multi-walled carbon nanotubes (MWNTs) has been synthesized using cyclic voltammetry (CV) under ambient conditions.…”
mentioning
confidence: 99%
“…Recently, Hirshberg [11]has theoretically predicted a novel metastable molecular crystal at ambient pressure, which is consisting of N 8 molecules. In addition, in 2008 Abou-Rachid et al [12,13] theoretically proposed that, the polymeric nitrogen N 8 as a chain could be encapsulated in the carbon nanotubes confinement at ambient pressure and room temperature. In 2014, Wang et al [14].…”
Section: Introductionmentioning
confidence: 99%